Dietary changes and associations with metabolic improvements in adults with type 2 diabetes during a patient-centred dietary intervention: an exploratory analysis. Issue 6 (13th June 2014) - England, C Y; Thompson, J L; Jago, R; Cooper, A R; Andrews, R C
Abstract : Objectives: Describe dietary intake of participants enrolled in a non-prescriptive dietary intervention and dietary changes at 6 months and explore whether these changes had a role in observed improvements in glycated haemoglobin (HbA1c), weight, lipids and blood pressure. Design: Secondary analysis of data from the Early ACTivity in Diabetes randomised controlled trial. Participants: 262 patients with newly diagnosed type 2 diabetes randomised to the dietary intervention. Outcomes and analysis: Changes in energy intake, macronutrients, fibre and alcohol and in weight, waist circumference, lipids, HbA1c and blood pressure at baseline and 6 months. Multivariate models were used to examine associations between dietary changes and metabolic variables. Results: Men reported reducing mean energy intake from 1903±462 kcal to 1685 kcal±439 kcal (p<0.001), increasing carbohydrate intake from 42.4±6.6% to 43.8±6.6% (p=0.002) and reducing median alcohol intake from 13 (0–27) g to 5 (0–18) g (p<0.001). Women reported reducing mean energy intake from 1582±379 kcal to 1459±326 kcal (p<0.001) with no change to macronutrient distribution and alcohol. Fibre intake was maintained. In men (n=148), weak and clinically insignificant associations were found between increased carbohydrates and reduction in HbA1c (β=−0.003 (−0.006, −0.001); p=0.009), increased fibre and reduction in total cholesterol (β=−0.023 (−0.044, −0.002); p=0.033), decreased total fat and reduction in low-density lipoprotein (LDL)-cholesterol (β=0.024 (0.006, 0.001); p=0.011), and decreased alcohol and reduction in diastolic blood pressure (β=0.276 (0.055, 0.497); p=0.015). In women (n=75), associations were found between a decrease in transfats and reductions in waist circumference (β=−0.029 (0.006, 0.052); p=0.015), total cholesterol (β=0.399 (0.028, 0.770); p=0.036) and LDL cholesterol (β=0.365 (0.042, 0.668); p=0.028). Conclusions: Clinically important metabolic improvements observed in a patient-centred dietary intervention were not explained by changes in macronutrients. However, a non-prescriptive approach may promote a reduction in total energy intake while maintaining fibre consumption. Trial registration number: The Early ACTID trial number ISRCTN92162869 .